Novel Insights into Pigment Composition and Molecular Mechanisms Governing Flower Coloration in Rose Cultivars Exhibiting Diverse Petal Hues - Yingxia Cheng; Yanling Tian; Pengyu Guo; Junjie Luo; Chan Xu; Yang Zhang; Guoping Chen; Qiaoli Xie; Zongli Hu (Plants)
The pigmentation of various components leads to different colors of roses. However, the intricate molecular machinery and metabolic pathways underlying rose pigmentation remain largely unexplored. In this study, we determined that pink and black-red petals contain abundant anthocyanins, reaching concentrations of 800 μg/g and 1400 μg/g, respectively, significantly surpassing those in white and yellow petals. We identified 22 key anthocyanin components, predominantly cyanidin, pelargonidin, delphinidin, peonidin, and petunidin, which were preferentially enriched in pink and black-red petals. Additionally, we confirmed the presence of five carotenoid species—lutein, zeaxanthin, ζ-carotene, α-carotene, and β-carotene—with zeaxanthin and carotenoids notably accumulating in yellow petals at significantly higher levels compared with other colors. Furthermore, RNA-seq and qRT-PCR analyses revealed the association between pigment accumulation and the expression patterns of genes involved in anthocyanin and carotenoid biosynthesis pathways. Through promoter core element prediction and transcriptional metabolic co-expression analyses, we found that the MYB transcription factor likely positively modulates the expressions of key biosynthetic genes such as CHS, F3′H, and DFR, while the NAC transcription factor enhances the transcriptional activities of PSY, ZISO, and LYCB. Overall, this study explores the components of flower color, unravels the synthesis of anthocyanins and carotenoids, identifies regulatory factors, and highlights the prospects of rose breeding.